Komparasi Hasil Belajar Matematika Ditinjau Dari Bentuk Soal Pilihan Ganda Dan Bentuk Soal Essay Pada Siwa Kelas V11 SMPN 2 Kebakkramat Tahun 2015/2016 - SEPTYANI, SINTA, Idris Harta, MA. Ph.D (2016)
This research aims to determine the differences of mathematics learning outcomes in terms of the form of multiple choice questions and essay form. This research is a comparative study. The population in this study were all students of class VII SMP N 2 Kebakkramat Year 2015/2016 a number of 224 students (7th grade), which consists of VII A, VII B, VII C, VII D, VII E, VII F and VII G. Sample in this study were 32 students of class VII F and 32 students of class VII G. data collection method used in this research is to test and documentation. Data analysis technique used is the t test previously conducted tests of normality and homogeneity test. From the results of data analysis with α = 5% concluded "there are differences in mathematics learning outcomes in terms of the form of multiple choice questions and essay form with t = 4.975. Results of studying mathematics with a form of multiple choice questions higher.